Hemeoxigenase-1 Genetic Variants Effects On Breast Cancer Progression - Schweitzer, Karen (2024)
Hemoxygenase-1 (HO-1) is a microsomal enzyme that catalyzes the degradation of the heme group (canonical role) and can be cleaved at its C-terminal end, followed by translocation to the nucleus, to perform functions at the transcriptional level (non-canonical role). Our laboratory has already demonstrated that HO-1 has antitumoral activity in breast cancer (BC) and that nuclear HO-1 is not enzymatically active. The aim of this work was to study the effect of genetic overexpression of HO-1 variants on cellular processes related to cancer progression, and the molecular mechanisms through which HO-1 modulates the cellular processes investigated. To accomplish this goal, we used the hormone- dependent BC cell line T47D and the triple-negative BC cell lines 4T1 and MDA-MB-231. These cell lines were stably transfected with plasmids overexpressing the HO-1 variants (full-length (FL-HO1), full-length without enzymatic activity (H25A-HO1) and truncated (T-HO1)). We observed significant differences in cell viability between wild-type (WT) cells and cells overexpressing HO-1 variants in the three cell lines evaluated (p<0.05, two-way ANOVA). We found that the WT cell line displays a higher rate of proliferation than those that overexpress FL in the three cell lines analyzed. However, the T-HO1 form behaves differently among cell lines, displaying more proliferative activity in 4T1 and MDA- MB-231 than in T47D cells. The H25A form appear to behave in the same way among cell lines, showing a similar phenotype to WT cells. These results indicate that the overexpression of HO-1 FL seems to display an anti-tumor role. The behavior of the H25A and the T-HO1 variants would indicate that the anti-tumor behavior is the result of both HO-1 enzymatic activity and its nuclear localization. In addition, cell line hormone-dependency would also contribute to the differential effects. Altogether, these results provide evidence of the canonical and non-canonical roles of HO-1 in BC.